Marketing / Principles and Practice - Adcock Dennis; Bradfield Ray; Halborg Al; Ross Caroline (Pitman Publishing, 1993)
Marketing is introduced both as a concept and as an organizational function of Management. What is Marketing, Products and Services and Benefits, The Marketing Environment, The Competitive Environment, Buyer Behavior, Segmentation of Markets, The Marketing-Environment, Marketing Information, Research for Marketing, Market Research, Positioning and the Marketing Mix, Product Policy, New Product Policy, New Product Development, Price and Quality and Value, Making Products Available, Marketing Communications, Promotional Planning, Advertising and Direct Marketing, Publicity and Sales Promotion and Sponsorship, Personal Selling, Marketing and Planning and Control, Consumerism and Social Responsibility and Ethics and Marketing, Marketing in Action.